A visão do jovem manauense do ensino médio sobre a velhice e o envelhecimento - Martinez, Yêda Lenir Henriques das Neves (2007)
This study investigates the social representations of the youth manauense, student of the medium teaching, on the old and the old age, establishing relationship between the historical data and the construction of the social thought on the theme, being looked for to identify the way those representations is expressed in the social relationships and the influence of the education process in its formation. It is believed that the education could serve as extenuating to reduce the dissonance of values and ideas that cause tension among the different generations, and to know the aging process would be to make possible the youth an education returned for the reality, contributing to the change of paradigms and for to revert the social process of the seniors' depreciation in the Brazilian culture. Leaving of the analysis of the speech of the subjects, its settled down a dialogue between the empiric data and the theoretical base, inside of a partner-historical and cultural perspective. The interpretative analysis, leaning in the hermenêutica-dialectics, its made data that corroborate the permanence to emerge, at the present time, of stereotypes related to the aging process, as well as the gap left by the education relatively to the theme in the youths' formation